Tsunami hazard in Turkey and surroundings - Necmioğlu, Öcal. (Thesis (Ph.D.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2014., 2014)
This study is an attempt to provide an overall assessment of the earthquake origin tsunami hazard in Turkey and its surroundings (Eastern Mediterranean, Aegean and Black Seas). To achieve this, I have first investigated the earthquake focal mechanism parameter variations effect into tsunami generation with special focus on Eastern Mediterranean. My analysis shows that, given the difficulty in accurately determining all focal mechanism parameters, tsunami hazard studies should look at a range of parameters, taking into consideration the maximum generated tsunami. If this broad study scope is not possible due to computational limitations, at least sensitivity studies, should be conducted, and parameters should be selected that would lead to maximum tsunami generation. An option would be to consider only strike and rake variations in the scenario databases as the key criteria in determining the worst-case scenario for a given forecast point, and if applicable, various earthquake depth ranges should be considered. Following this work, I have compiled all available information concerning earthquake source parameters and their regional characterization and attempted to define characteristic static earthquake source parameters for all tsunamigenic earthquakes in the region. I have identified a set of tsunami scenario input parameters in a 0.5° x 0.5° uniformly gridded area in the Eastern Mediterranean (both for shallow and intermediate depth earthquakes), Aegean and Black Seas (only shallow earthquakes) and calculated tsunami scenarios using SWAN-JRC (Annunziato, 2007) with 2-arcmin resolution bathymetry data for the range of 6.5 – Mwmax with a Mw increment of 0.1 at each grid in order to realize a comprehensive earthquake origin tsunami hazard analysis in the region based on the definition of the characteristic earthquake source parameters from a compiled set of sources such as existing moment tensor catalogs and various reference studies, together with the Mwmax assigned in the literature, where possible. Results from 2415 scenarios show that in Eastern Mediterranean and its connected seas (Aegean and Black Sea), shallow earthquakes with already Mw ≥ 6.5 may result in 0.5m coastal wave height, whereas same level of wave height could be expected only with Mw ≥ 7.0 for intermediate depth earthquakes. The distribution of maximum wave heights calculated indicate that tsunami wave heights up to 1m could be expected in northern Aegean, whereas in Black Sea, Cyprus, Levantine coasts, northern Libya, eastern Sicily, southern Italy, and western Greece, up to 3m wave height could be possible. Crete, southern Aegean, and the area between northeast Libya and Alexandria (Egypt) is prone to high level of tsunami hazard with Hw > 3m wave heights calculated. Considering that calculations are performed at a minimum bathymetry depth of 20 m, these wave heights may amplify by a factor of 2 at the coastline according to Green’s Law. On the other hand, it should be emphasized that while the Green’s Law provide an empirical approximation, the non-linear dynamics of the tsunami at the coastal zones may lead to deviations in actual wave heights. As an overall conclusion, my analysis indicate that in Black Sea, locations in the southern coasts of Crimea, northwestern coast of Turkey, Bulgarian coast and southeastern coasts of Romania are prone to considerable (1m < Hw < 3m) level of tsunami hazard, whereas the eastern Black Sea coasts could be considered as low (Hw < 1m) tsunami hazard zones. Concerning Eastern-Central Mediterranean and Aegean Seas, my study indicate that locations in, around and orthogonal to the Hellenic Arc are prone to high (Hw > 3m) level of tsunami hazard, whereas the tsunami hazard should be identified as considerable (1m < Hw < 3m) for the rest of the Eastern Mediterranean, Southern Aegean, Tripoli (Libya), eastern Sicily, Calabria, western coasts Greece, Antalya Peninsula and Bay western and southern Cyprus and southern Levantine coast. Tsunami hazard can be classified as relatively low for the northern Aegean, Tunisia, western Sardinia, southwest coasts of Italy, and western and northern coasts of Sicily. The results of the modeling are in accordance with the historical tsunami events in the study area. It should be emphasized that these conclusions are valid only for the earthquake sources considered in this study excluding any possibility of a triggered submarine landslide. In addition to the work describe above, I have also exploited several reliable tsunami catalogs (Ambraseys, 1962 and 2009; Soloviev, 2000; Fokaefs and Papadopoulos, 2007; Altinok et al., 2011, Papadopoulos et al., 2012) by performing a cross-comparison of the events in order to create a harmonized database for the study area. The reliability of the tsunami occurrence has been defined as Unlikely (U), Questionable (Q), Probable (P) and Definite (D), where improbable events were removed. There are 145 events in the harmonized database, where 41 events are defined as definite, 30 events as possible, 58 events as questionable and 16 events as unlikely. 44 events include contradicting information from selected source databases.
Keywords: Tsunamis -- Turkey.; Tsunamis -- Mathematical models.